2014
DOI: 10.3743/kosim.2014.31.3.293
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis on Twitter Research

Abstract: This study explored the research trends on Twitter in Korea by informetric methods. All 539 articles on Twitter published from 2009 to the April of 2014 were obtained from the KCI. Only article titles, abstracts, and keywords by authors were used in analysis. Academic journals in many different disciplines where Twitter articles were produced were analysed by profiling, and then, the subject areas of researches on Twitter were analysed by co-word analysis. The results of this study showed that Twitter-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…One of the most discussed research field of Twitter was its implication on political issues [10], recent years, scholars have argued the influence of using Twitter in sociopolitical movements [11][12][13], in political elections and campaigns [14][15][16]. Despite the fact that how much influence Twitter has in such events remains under discussion, scholars' enthusiasm toward Twitter in politics seems increasing.…”
Section: Twitter and Its Research Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most discussed research field of Twitter was its implication on political issues [10], recent years, scholars have argued the influence of using Twitter in sociopolitical movements [11][12][13], in political elections and campaigns [14][15][16]. Despite the fact that how much influence Twitter has in such events remains under discussion, scholars' enthusiasm toward Twitter in politics seems increasing.…”
Section: Twitter and Its Research Linesmentioning
confidence: 99%
“…There are some academic works focusing on this issue; for example, Williams, Terras and Warwick [9] qualitatively reviewed the title and abstract of 1161 Twitter-related articles, they classified these remaining academic works across three dimensions: aspect, method and domain, they found that the majority of the publications relating to Twitter concentrates on messages sent and details of the users. Kang and Lee [10] applied a co-word analysis to a limited bibliographic data of the Korea Citation Index, revealing 53 different disciplines in Twitter scientific literatures. Gupta et al [7] quantitatively ranked 4709 Twitter-related studies by various categories, including annual global publication, geographic distribution, subject distribution, top keywords, top productive institutions, top authors etc.…”
Section: Introductionmentioning
confidence: 99%